Beneficial effects of endophytic fungi inoculation on tanshinones and phenolic compounds of Salvia abrotanoides - Fatemeh Khorasania; Ali Ganjeali; javad Asili; Monireh Cheniany (Iranian Journal of Basic Medical Sciences, 2023)
Objective(s): Salvia abrotanoides is considered as a new source of tanshinone-producing plants in Iran. Symbiosis of endophytic fungi with their host plants is an effective tool to promote the growth and secondary metabolism of medicinal herbs. Therefore, using endophytic fungi as a biotic elicitor is a proper solution to increase the yield of plant products. Materials and Methods: In this study, some endophytic fungi were first isolated from the root of S. abrotanoides, then two of them (Penicillium canescens and Talaromyces sp.) were co-cultivated with the sterile seedling of S. abrotanoides in pot culture. After proving the colonization of these fungi in the root tissues by microscopic studies, their effects on the production of critical medicinal compounds such as tanshinones and phenolic acids were investigated in the vegetation stage (120 days). Results: Our results showed that the content of cryptotanshinone (Cry) and tanshinone IIA (T-IIA) in plants inoculated with P.  canescens increased by 77.00% and 19.64%, respectively, compared with non-inoculated plants (control). The contents of mentioned compounds in plants inoculated with Talaromyces sp. increased by 50.00% and 23.00%, respectively. In this case, in plants inoculated with P. canescens, it was found that the level of caffeic acid, rosmarinic acid, and its PAL enzyme activity increased by 64.00%, 69.00%, and 50.00%, respectively, compared with the control.Conclusion: Endophytic fungi have specific modes of action and the ability to provide multiple benefits. Each of the two strains is a highly considerable microbial resource for the growth and accumulation of active compounds of S. abrotanoides.